Solid electrolyte material and battery using the same
By adding Li, Zr, Al and F to the solid electrolyte material, the composition and manufacturing process are optimized, and the problem of insufficient lithium ion conductivity and oxidation resistance in the prior art is solved, and a battery material with high lithium ion conductivity and excellent charging and discharge characteristics is achieved.
Patent Information
- Application Number
- CN202080096152.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-02-14
- Filing Date
- 2020-11-12
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2040-11-12
AI Technical Summary
The prior art is difficult to provide solid electrolyte materials with high lithium ion conductivity, especially in terms of safety and oxidation resistance.
The solid electrolyte material containing Li, Zr, Al and F is used to improve the lithium ion conductivity and oxidation resistance of the material through optimized composition and manufacturing process.
A solid electrolyte material with high lithium ion conductivity is achieved, ensuring excellent charging and discharging characteristics of the battery, and improving the safety and oxidation resistance of the material.
Smart Images

Figure CN115088111B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a solid electrolyte material and a battery using the same. Background Art
[0002] Patent Document 1 discloses an all-solid-state battery using a sulfide solid electrolyte. Patent Document 2 discloses LiBF4 as a fluoride solid electrolyte material.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2011-129312
[0006] Patent Document 2: Japanese Patent Application Publication No. 2008-277170 Summary of the invention
[0007] Problems to be solved by the invention
[0008] An object of the present disclosure is to provide a solid electrolyte material having high lithium ion conductivity.
[0009] Means for solving problems
[0010] The solid electrolyte material disclosed herein contains Li, Zr, Al, and F.
[0011] Effects of the Invention
[0012] The present disclosure provides a solid electrolyte material with high lithium ion conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 A cross-sectional view showing a battery 1000 according to a second embodiment.
[0014] Figure 2 A cross-sectional view showing a battery 2000 according to a second embodiment.
[0015] Figure 3 A schematic diagram showing a press mold 300 used to evaluate the ion conductivity of a solid electrolyte material.
[0016] Figure 4 This is a graph showing a Cole-Cole plot of the solid electrolyte material of Example 1 obtained by impedance measurement.
[0017] Figure 5 It is a graph showing the initial discharge characteristics of the batteries of Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0018] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings.
[0019] (First embodiment)
[0020] The solid electrolyte material of the first embodiment contains Li, Zr, Al, and F. The solid electrolyte material of the first embodiment has a high lithium ion conductivity. Here, the so-called high lithium ion conductivity is, for example, 8×10 -9 S / cm or more. That is, the solid electrolyte material of the first embodiment may have, for example, 8×10 -9 S / cm or higher ion conductivity.
[0021] The solid electrolyte material of the first embodiment can be used to obtain a battery having excellent charge and discharge characteristics. An example of such a battery is an all-solid battery. The all-solid battery may be a primary battery or a secondary battery.
[0022] The solid electrolyte material of the first embodiment is preferably substantially free of sulfur. The so-called solid electrolyte material of the first embodiment is substantially free of sulfur, which means that the solid electrolyte material does not contain sulfur as a constituent element except for sulfur inevitably mixed in as an impurity. In this case, the sulfur mixed in the solid electrolyte material as an impurity is, for example, 1 mol% or less. From the viewpoint of safety, the solid electrolyte material of the first embodiment is preferably free of sulfur. The sulfur-free solid electrolyte material has excellent safety because hydrogen sulfide will not be generated even if exposed to the atmosphere. The sulfide solid electrolyte disclosed in Patent Document 1 may generate hydrogen sulfide if exposed to the atmosphere.
[0023] The solid electrolyte material of the first embodiment can have a high oxidation resistance due to the inclusion of F. This is because F has a high redox potential. On the other hand, since F has a high electronegativity, it binds strongly to Li. As a result, the lithium ion conductivity of the solid electrolyte material containing Li and F is generally reduced. For example, LiBF4 disclosed in Patent Document 2 has a conductivity of 6.67×10 -9 S / cm. In contrast, the solid electrolyte material of the first embodiment can have a low ion conductivity of, for example, 8×10 -9 S / cm or more, and 1×10 -8 S / cm or higher ion conductivity.
[0024] In order to improve the ion conductivity of the solid electrolyte material, the solid electrolyte material of the first embodiment may further contain anions other than F. Examples of the anions include Cl, Br, I, O, S, or Se.
[0025] In order to improve the oxidation resistance of the solid electrolyte material, the ratio of the amount of substance of F constituting the solid electrolyte material of the first embodiment to the total amount of substance of anions may be 0.50 or more and 1.0 or less.
[0026] The solid electrolyte material of the first embodiment may also be substantially composed of Li, Zr, Al and F. Here, the so-called "the solid electrolyte material of the first embodiment is substantially composed of Li, Zr, Al and F" means that the molar ratio (i.e., molar fraction) of the total amount of Li, Zr, Al and F constituting the solid electrolyte material of the first embodiment relative to the total amount of all elements is 90% or more. As an example, the molar ratio (i.e., molar fraction) may also be 95% or more. The solid electrolyte material of the first embodiment may also be composed of only Li, Zr, Al and F.
[0027] The solid electrolyte material of the first embodiment may contain an element that is inevitably mixed in. Examples of such an element are hydrogen, oxygen, or nitrogen. Such an element may be present in the raw material powder of the solid electrolyte material or in the atmosphere used to manufacture or store the solid electrolyte material.
[0028] In order to further improve the ion conductivity of the solid electrolyte material, in the solid electrolyte material of the first embodiment, the ratio of the amount of Li to the total amount of Zr and Al may be 1.12 to 5.07.
[0029] The solid electrolyte material according to the first embodiment can also be represented by the following composition formula (1).
[0030] Li 6-(4-x)b (Zr 1-x Al x ) b F6 formula (1)
[0031] In formula (1), the mathematical formulas: 0<x<1 and 0<b≤1.5 may be satisfied. Such a solid electrolyte material has a high ion conductivity.
[0032] In order to improve the ion conductivity of the solid electrolyte material, in formula (1), the mathematical formula: 0.01≤x≤0.99 may be satisfied, and preferably the mathematical formula: 0.2≤x≤0.95 may be satisfied.
[0033] The upper limit and lower limit of the range of x in formula (1) can be defined by any combination of numerical values selected from 0.01, 0.2, 0.4, 0.5, 0.5, 0.7, 0.8, 0.95, and 0.99.
[0034] In order to improve the ion conductivity of the solid electrolyte material, in formula (1), the mathematical formula: 0.7≤b≤1.3 may be satisfied, and preferably the mathematical formula: 0.9≤b≤1.04 may be satisfied.
[0035] The upper limit and lower limit of the range of b in formula (1) can be defined by any combination of numerical values selected from 0.7, 0.8, 0.9, 0.96, 1, 1.04, 1.1, 1.2, and 1.3.
[0036] The solid electrolyte material of the first embodiment may be crystalline or amorphous.
[0037] The shape of the solid electrolyte material of the first embodiment is not limited. Examples of the shape are needle-shaped, spherical, or ellipsoidal. The solid electrolyte material of the first embodiment may also be particles. The solid electrolyte material of the first embodiment may also be formed in a pellet or plate shape.
[0038] When the shape of the solid electrolyte material of the first embodiment is, for example, granular (e.g., spherical), the solid electrolyte material may also have a median particle size of 0.1 μm or more and 100 μm or less. The so-called median particle size means the particle size when the cumulative volume in the volume-based particle size distribution is equal to 50%. The volume-based particle size distribution can be measured, for example, by a laser diffraction measuring device or an image analysis device.
[0039] The solid electrolyte material of the first embodiment may also have a median particle size of 0.5 μm or more and 10 μm or less. Thus, the solid electrolyte material has higher conductivity. In addition, when the solid electrolyte material of the first embodiment is mixed with other materials such as active materials, the dispersion state of the solid electrolyte material of the first embodiment and other materials becomes good.
[0040] <Method for producing solid electrolyte material>
[0041] The solid electrolyte material of the first embodiment can be produced by, for example, the following method.
[0042] Raw material powders are prepared and mixed so as to achieve a target composition. The raw material powders may be halides, for example.
[0043] As an example, when the target composition is Li 2.64 Zr 0.48 Al 0.48 In F6, LiF, ZrF4 and AlF3 are mixed in a molar ratio of about 2.64:0.48:0.48. In order to offset the composition changes that may occur during the synthesis process, the raw material powders can also be mixed in a pre-adjusted molar ratio.
[0044] The raw powders are reacted with each other in a mechanochemical manner (that is, using a mechanochemical grinding method) in a mixing device such as a planetary ball mill to obtain a reactant. The reactant may also be calcined in a vacuum or in an inert atmosphere. Alternatively, the reactant may be obtained by calcining a mixture of raw powders in a vacuum or in an inert atmosphere. Calcination is preferably performed at a temperature of, for example, 100° C. or more and 400° C. or less for more than 1 hour. In order to suppress composition changes during calcination, the raw powders may also be calcined in a sealed container such as a quartz tube.
[0045] By these methods, the solid electrolyte material of the first embodiment can be obtained.
[0046] The composition of the solid electrolyte material can be determined, for example, by ICP emission spectrometry, ion chromatography, inert gas fusion-infrared absorption or EPMA (Electron Probe Micro Analyzer). For example, the composition of Li, Zr and Al can be determined by ICP emission spectrometry, and the composition of F can be determined by ion chromatography.
[0047] (Second embodiment)
[0048] The second embodiment will be described below. Matters described in the first embodiment may be omitted.
[0049] The battery of the second embodiment comprises a positive electrode, a negative electrode and an electrolyte layer. The electrolyte layer is provided between the positive electrode and the negative electrode. At least one selected from the positive electrode, the electrolyte layer and the negative electrode contains the solid electrolyte material of the first embodiment. The battery of the second embodiment has excellent charge and discharge characteristics because it contains the solid electrolyte material of the first embodiment. The battery may also be an all-solid battery.
[0050] Figure 1 A cross-sectional view showing a battery 1000 according to a second embodiment.
[0051] The battery 1000 of the second embodiment includes a positive electrode 201 , an electrolyte layer 202 , and a negative electrode 203 . The electrolyte layer 202 is provided between the positive electrode 201 and the negative electrode 203 .
[0052] The positive electrode 201 includes positive electrode active material particles 204 and solid electrolyte particles 100 .
[0053] The electrolyte layer 202 contains an electrolyte material. The electrolyte material is, for example, a solid electrolyte material.
[0054] The negative electrode 203 includes negative electrode active material particles 205 and solid electrolyte particles 100 .
[0055] The solid electrolyte particle 100 is a particle containing the solid electrolyte material of the first embodiment. The solid electrolyte particle 100 may also be a particle composed of the solid electrolyte material of the first embodiment or a particle containing the solid electrolyte material of the first embodiment as a main component. Here, the particle containing the solid electrolyte material of the first embodiment as a main component means a particle containing the solid electrolyte material of the first embodiment as the largest component in terms of molar ratio.
[0056] The positive electrode 201 contains a material that can insert and remove metal ions (such as lithium ions), such as a positive electrode active material (such as positive electrode active material particles 204).
[0057] Examples of positive electrode active materials include lithium-containing transition metal oxides, transition metal fluorides, polyanion materials, fluorinated polyanion materials, transition metal sulfides, transition metal sulfur oxides or transition metal nitrogen oxides. Examples of lithium-containing transition metal oxides include Li(Ni, Co, Al)O2, Li(Ni, Co, Mn)O2 or LiCoO2. In the present disclosure, the symbol "(Ni, Co, Al)" in the chemical formula represents at least one element selected from the element group in brackets. That is, "(Ni, Co, Al)" is synonymous with "at least one selected from Ni, Co and Al". The same applies to other elements.
[0058] The positive electrode active material particles 204 may also have a median particle size of 0.1 μm or more and 100 μm or less. When the positive electrode active material particles 204 have a median particle size of 0.1 μm or more, the dispersion state of the positive electrode active material particles 204 and the solid electrolyte particles 100 in the positive electrode 201 becomes good. As a result, the charge and discharge characteristics of the battery are improved. When the positive electrode active material particles 204 have a median particle size of 100 μm or less, the lithium diffusion rate in the positive electrode active material particles 204 is increased. As a result, the battery can operate at a high output power.
[0059] The positive electrode active material particles 204 may have a larger median diameter than the solid electrolyte particles 100. This improves the dispersion state of the positive electrode active material particles 204 and the solid electrolyte particles 100 in the positive electrode 201.
[0060] From the viewpoint of battery energy density and output, in the positive electrode 201 , the ratio of the volume of the positive electrode active material particles 204 to the total volume of the positive electrode active material particles 204 and the volume of the solid electrolyte particles 100 may be 0.30 or more and 0.95 or less.
[0061] A coating layer may also be formed on at least a portion of the surface of the positive electrode active material particle 204. The coating layer may be formed on the surface of the positive electrode active material particle 204, for example, before being mixed with the conductive aid and the binder. Examples of the coating material contained in the coating layer include a sulfide solid electrolyte, an oxide solid electrolyte, or a halide solid electrolyte. When the solid electrolyte particle 100 contains a sulfide solid electrolyte, in order to suppress the oxidative decomposition of the sulfide solid electrolyte, the coating material may also contain the solid electrolyte material of the first embodiment. When the solid electrolyte particle 100 contains the solid electrolyte material of the first embodiment, in order to suppress the oxidative decomposition of the solid electrolyte material, the coating material may also contain an oxide solid electrolyte. As the oxide solid electrolyte, lithium niobate, which has excellent stability at high potential, may also be used. By suppressing the oxidative decomposition of the solid electrolyte material, the increase in the overvoltage of the battery can be suppressed.
[0062] From the viewpoint of the energy density and output of the battery, the positive electrode 201 may have a thickness of 10 μm or more and 500 μm or less.
[0063] The electrolyte layer 202 contains an electrolyte material. The electrolyte material is, for example, a solid electrolyte material. The electrolyte layer 202 may also be a solid electrolyte layer.
[0064] The electrolyte layer 202 may also contain the solid electrolyte material of the first embodiment. The electrolyte layer 202 may also be composed only of the solid electrolyte material of the first embodiment. The electrolyte layer 202 may also be composed only of a solid electrolyte material different from the solid electrolyte material of the first embodiment. Examples of solid electrolyte materials different from the solid electrolyte material of the first embodiment include Li2MgX4, Li2FeX4, Li(Al, Ga, In)X4, Li3(Al, Ga, In)X6, or LiI. Here, X is at least one selected from F, Cl, Br, and I.
[0065] Hereinafter, the solid electrolyte material of the first embodiment is referred to as a first solid electrolyte material. A solid electrolyte material different from the solid electrolyte material of the first embodiment is referred to as a second solid electrolyte material.
[0066] The electrolyte layer 202 may contain not only the first solid electrolyte material but also the second solid electrolyte material. The first solid electrolyte material and the second solid electrolyte material may be uniformly dispersed in the electrolyte layer 202. A layer formed of the first solid electrolyte material and a layer formed of the second solid electrolyte material may be stacked along the stacking direction of the battery 1000.
[0067] Figure 2 A cross-sectional view showing a battery 2000 according to a second embodiment.
[0068] like Figure 2 As shown, the battery 2000 may also include a positive electrode 201, a first electrolyte layer 212, a second electrolyte layer 222, and a negative electrode 203. That is, the electrolyte layer 202 may also include a first electrolyte layer 212 and a second electrolyte layer 222. The first electrolyte layer 212 is disposed between the positive electrode 201 and the negative electrode 203. The second electrolyte layer 222 is disposed between the first electrolyte layer 212 and the negative electrode 203.
[0069] In the battery 2000, the first electrolyte layer 212 may also contain the solid electrolyte material of the first embodiment. Since the solid electrolyte material of the first embodiment has high oxidation resistance, the solid electrolyte material contained in the second electrolyte layer 222 can be used without oxidation. As a result, the charge and discharge efficiency of the battery can be improved.
[0070] In the battery 2000, the solid electrolyte material contained in the second electrolyte layer 222 may have a lower reduction potential than the solid electrolyte material contained in the first electrolyte layer 212. Thus, the solid electrolyte material contained in the first electrolyte layer 212 can be used without being reduced. As a result, the charge and discharge efficiency of the battery can be improved. For example, when the first electrolyte layer 212 contains the solid electrolyte material of the first embodiment, in order to suppress the reduction decomposition of the solid electrolyte material, the second electrolyte layer 222 may also contain a sulfide solid electrolyte.
[0071] From the viewpoint of the energy density and output of the battery, the electrolyte layer 202 may have a thickness of 1 μm or more and 1000 μm or less.
[0072] The negative electrode 203 contains a material that can insert and remove metal ions (such as lithium ions), such as a negative electrode active material (such as negative electrode active material particles 205).
[0073] Examples of negative electrode active materials include metal materials, carbon materials, oxides, nitrides, tin compounds or silicon compounds. The metal material may be a simple metal or an alloy. Examples of metal materials are lithium metal or lithium alloys. Examples of carbon materials include natural graphite, coke, graphitizable carbon, carbon fiber, spherical carbon, artificial graphite or amorphous carbon. From the viewpoint of capacity density, suitable examples of negative electrode active materials include silicon (i.e., Si), tin (i.e., Sn), silicon compounds or tin compounds.
[0074] The negative electrode active material may also be selected in consideration of the reduction resistance of the solid electrolyte material contained in the negative electrode 203. For example, when the negative electrode 203 contains the solid electrolyte material of the first embodiment, the negative electrode active material may also be a material that can intercalate and deintercalate lithium ions at a voltage of 0.27 V or more relative to lithium. Examples of such negative electrode active materials include titanium oxide, indium metal, or lithium alloy. Examples of titanium oxide include Li4Ti5O 12 , LiTi2O4 or TiO2. By using the above-mentioned negative electrode active material, the reductive decomposition of the solid electrolyte material of the first embodiment contained in the negative electrode 203 can be suppressed. As a result, the charge and discharge efficiency of the battery can be improved.
[0075] The negative electrode active material particles 205 may also have a median particle size of 0.1 μm or more and 100 μm or less. When the negative electrode active material particles 205 have a median particle size of 0.1 μm or more, the dispersion state of the negative electrode active material particles 205 and the solid electrolyte particles 100 in the negative electrode 203 becomes good. As a result, the charge and discharge characteristics of the battery are improved. When the negative electrode active material particles 205 have a median particle size of 100 μm or less, the lithium diffusion rate in the negative electrode active material particles 205 is increased. As a result, the battery can operate at a high output power.
[0076] The negative electrode active material particles 205 may have a larger median diameter than the solid electrolyte particles 100. This improves the dispersion state of the negative electrode active material particles 205 and the solid electrolyte particles 100 in the negative electrode 203.
[0077] From the viewpoint of battery energy density and output, in the negative electrode 203 , the ratio of the volume of the negative electrode active material particles 205 to the total volume of the negative electrode active material particles 205 and the volume of the solid electrolyte particles 100 may be 0.30 or more and 0.95 or less.
[0078] From the viewpoint of the energy density and output of the battery, the negative electrode 203 may have a thickness of 10 μm or more and 500 μm or less.
[0079] At least one selected from the positive electrode 201, the electrolyte layer 202 and the negative electrode 203 may also contain a second solid electrolyte material for the purpose of improving ion conductivity, chemical stability and electrochemical stability. Examples of the second solid electrolyte material include sulfide solid electrolytes, oxide solid electrolytes, halide solid electrolytes or organic polymer solid electrolytes.
[0080] In the present disclosure, "sulfide solid electrolyte" means a solid electrolyte containing sulfur. "Oxide solid electrolyte" means a solid electrolyte containing oxygen. The oxide solid electrolyte may also contain anions other than oxygen (except sulfur anions and halogen anions). "Halide solid electrolyte" means a solid electrolyte containing halogen elements and no sulfur. The halide solid electrolyte may contain not only halogen elements but also oxygen.
[0081] The second solid electrolyte material may be a sulfide solid electrolyte.
[0082] Examples of sulfide solid electrolytes include Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, Li 3.25 Ge 0.25 P 0.75 S4 or Li 10 GeP2S 12 .
[0083] When the electrolyte layer 202 contains the solid electrolyte material of the first embodiment, the negative electrode 203 may also contain a sulfide solid electrolyte in order to suppress the reduction decomposition of the solid electrolyte material. By coating the negative electrode active material with an electrochemically stable sulfide solid electrolyte, the solid electrolyte material of the first embodiment can be suppressed from contacting the negative electrode active material. As a result, the internal resistance of the battery can be reduced.
[0084] The second solid electrolyte material may be an oxide solid electrolyte.
[0085] Examples of oxide solid electrolytes are:
[0086] (i) NASICON type solid electrolytes such as LiTi2(PO4)3 or its element substitution products,
[0087] (ii) Perovskite-type solid electrolytes such as (LaLi)TiO3,
[0088] (iii)Li 14 ZnGe4O 16 , LISICON type solid electrolytes such as Li4SiO4, LiGeO4 or their element substitution products,
[0089] (iv)Li7La3Zr2O 12 or a garnet-type solid electrolyte such as an element substitution body thereof, or
[0090] (v) Li3PO4 or its N-substituted form.
[0091] As described above, the second solid electrolyte material may be a halide solid electrolyte.
[0092] Examples of halide solid electrolytes include Li2MgX4, Li2FeX4, Li(Al, Ga, In)X4, Li3(Al, Ga, In)X6 or LiI. Here, X is at least one selected from F, Cl, Br and I.
[0093] Other examples of halide solid electrolyte materials are Li a Me b Y c A compound represented by X6. Here, a+mb+3c=6 and c>0 are satisfied. Me is at least one selected from metal elements and semi-metal elements other than Li and Y. m represents the valence of Me. The so-called "semi-metal elements" are B, Si, Ge, As, Sb and Te. The so-called "metal elements" are all elements contained in Groups 1 to 12 of the periodic table (except hydrogen) and all elements contained in Groups 13 to 16 of the periodic table (except B, Si, Ge, As, Sb, Te, C, N, P, O, S and Se).
[0094] In order to improve the ion conductivity of the halide solid electrolyte material, Me may be at least one selected from Mg, Ca, Sr, Ba, Zn, Sc, Al, Ga, Bi, Zr, Hf, Ti, Sn, Ta and Nb. The halide solid electrolyte may also be Li3YCl6 or Li3YBr6.
[0095] The second solid electrolyte material may also be an organic polymer solid electrolyte.
[0096] Examples of the organic polymer solid electrolyte include compounds of a polymer compound and a lithium salt.
[0097] The polymer compound may have an ethylene oxide structure. A polymer compound having an ethylene oxide structure can contain a large amount of lithium salt, and thus can further improve ion conductivity.
[0098] Examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9) or LiC(SO2CF3)3. One lithium salt selected from these may be used alone. Alternatively, a mixture of two or more lithium salts selected from these may be used.
[0099] At least one selected from the positive electrode 201 , the electrolyte layer 202 , and the negative electrode 203 may contain a non-aqueous electrolyte solution, a gel electrolyte, or an ionic liquid for the purpose of facilitating the transfer of lithium ions and improving the output characteristics of the battery.
[0100] The non-aqueous electrolyte contains a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent.
[0101] Examples of non-aqueous solvents include cyclic carbonate solvents, chain carbonate solvents, cyclic ether solvents, chain ether solvents, cyclic ester solvents, chain ester solvents or fluorinated solvents. Examples of cyclic carbonate solvents include ethylene carbonate, propylene carbonate or butylene carbonate. Examples of chain carbonate solvents include dimethyl carbonate, ethyl methyl carbonate or diethyl carbonate. Examples of cyclic ether solvents include tetrahydrofuran, 1,4-dioxane or 1,3-dioxolane. Examples of chain ether solvents include 1,2-dimethoxyethane or 1,2-diethoxyethane. Examples of cyclic ester solvents include γ-butyrolactone. Examples of chain ester solvents include methyl acetate. Examples of fluorinated solvents include fluoroethylene carbonate, methyl fluoropropionate, fluorobenzene, ethyl fluoromethyl carbonate or dimethylene fluorocarbonate. One non-aqueous solvent selected therefrom may be used alone. Alternatively, a combination of two or more non-aqueous solvents selected therefrom may be used.
[0102] Examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9) or LiC(SO2CF3)3. One lithium salt selected from these may be used alone. Alternatively, a mixture of two or more lithium salts selected from these may be used. The concentration of the lithium salt is, for example, in the range of 0.5 mol / L or more and 2 mol / L or less.
[0103] As the gel electrolyte, a polymer material impregnated with a non-aqueous electrolyte can be used. Examples of the polymer material include polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, or a polymer having a polyethylene oxide bond.
[0104] Examples of cations contained in ionic liquids are:
[0105] (i) aliphatic chain quaternary salts such as tetraalkylammonium or tetraalkylphosphonium,
[0106] (ii) an aliphatic cyclic ammonium such as pyrrolidinium, morpholinium, imidazolinium, tetrahydropyrimidinium, piperazinium or piperidinium, or
[0107] (iii) Nitrogen-containing heterocyclic aromatic cations such as pyridinium and imidazolium cations.
[0108] Examples of anions contained in ionic liquids include PF6 - 、BF4 - 、SbF6 - 、AsF6 - 、SO3CF3 -、N(SO2CF3)2 - 、N(SO2C2F5)2 - 、N(SO2CF3)(SO2C4F9) - or C(SO2CF3)3 - .
[0109] The ionic liquid may also contain a lithium salt.
[0110] At least one selected from the positive electrode 201 , the electrolyte layer 202 , and the negative electrode 203 may contain a binder for the purpose of improving the adhesion between particles.
[0111] The example of binding agent has polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamide-imide, polyacrylonitrile, polyacrylic acid, polymethyl acrylate, polyethyl acrylate, polyhexyl acrylate, polymethacrylic acid, polymethyl methacrylate, polyethyl methacrylate, polyhexyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyether, polyether sulfone, polyhexafluoropropylene, styrene-butadiene rubber or carboxymethyl cellulose. In addition, copolymer also can be used as binding agent. The example of such binding agent has the copolymer of the material of more than two kinds selected from tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, chlorotrifluoroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid and hexadiene. As binding agent, the mixture of the material of more than two kinds can also be used.
[0112] At least one of the positive electrode 201 and the negative electrode 203 may contain a conductive auxiliary agent in order to reduce electronic resistance.
[0113] Examples of conductive additives are:
[0114] (i) Graphites such as natural graphite or artificial graphite,
[0115] (ii) Carbon blacks such as acetylene black or Ketjen black,
[0116] (iii) Conductive fibers such as carbon fibers or metal fibers,
[0117] (iv) fluorinated carbon,
[0118] (v) Metal powders such as aluminum,
[0119] (vi) Conductive whiskers such as zinc oxide or potassium titanate,
[0120] (vii) conductive metal oxides such as titanium oxide, or
[0121] (viii) Conductive polymer compounds such as polyaniline, polypyrrole or polythiophene.
[0122] For the purpose of cost reduction, the conductive auxiliary agent (i) or (ii) mentioned above may be used.
[0123] Examples of the shape of the battery of the second embodiment include a coin shape, a cylindrical shape, a square shape, a sheet shape, a button shape, a flat shape, or a laminated shape.
[0124] The battery of the second embodiment can also be manufactured, for example, by preparing a positive electrode forming material, an electrolyte layer forming material, and a negative electrode forming material, and producing a stacked body in which a positive electrode, an electrolyte layer, and a negative electrode are arranged in this order by a known method.
[0125] Example
[0126] Hereinafter, the present disclosure will be described in more detail with reference to Examples and Comparative Examples.
[0127] <Example 1>
[0128] (Production of solid electrolyte materials)
[0129] In an argon atmosphere with a dew point below -60°C (hereinafter referred to as "dry argon atmosphere"), LiF, ZrF4 and AlF3 are prepared as raw material powders in a molar ratio of LiF: ZrF4: AlF3 = 2.5: 0.5: 0.5. These raw material powders are crushed and mixed in a mortar. The obtained mixed powder is ground at 500 rpm for 12 hours using a planetary ball mill. In this way, a powder of the solid electrolyte material of Example 1 is obtained. The solid electrolyte material of Example 1 has a Li 2.5 Zr 0.5 Al 0.5 F6 represents the composition.
[0130] (Evaluation of ion conductivity)
[0131] Figure 3 A schematic diagram showing a press mold 300 used to evaluate the ion conductivity of a solid electrolyte material.
[0132] The press forming die 300 includes a punch upper portion 301, a frame die 302, and a punch lower portion 303. The frame die 302 is formed of insulating polycarbonate. The punch upper portion 301 and the punch lower portion 303 are formed of electronically conductive stainless steel.
[0133] use Figure 3 The press molding die 300 shown was used to evaluate the ion conductivity of the solid electrolyte material of Example 1 by the following method.
[0134] In a dry atmosphere having a dew point of -30°C or less, the powder of the solid electrolyte material of Example 1 was filled into the press die 300. Inside the press die 300, a pressure of 400 MPa was applied to the solid electrolyte material of Example 1 using the punch upper portion 301 and the punch lower portion 303.
[0135] The punch upper part 301 and the punch lower part 303 were connected to a potentiostat (Versa STAT4 manufactured by Princeton Applied Research) equipped with a frequency response analyzer while maintaining the pressure. The punch upper part 301 was connected to the working electrode and the potential measurement terminal. The punch lower part 303 was connected to the counter electrode and the reference electrode. The impedance of the solid electrolyte material was measured by electrochemical impedance spectroscopy at room temperature.
[0136] Figure 4 This is a graph showing a Cole-Cole plot obtained by impedance measurement of the solid electrolyte material of Example 1.
[0137] Figure 4 In the equation, the real value of the impedance at the measurement point where the absolute value of the phase of the complex impedance is the smallest is regarded as the resistance value of the solid electrolyte material to ion conduction. For this real value, please refer to Figure 4 The arrow R shown in SE Using this resistance value, the ion conductivity was calculated based on the following mathematical formula (2).
[0138] σ=(R SE ×S / t) -1 (2)
[0139] Here, σ represents ion conductivity. S represents the contact area between the solid electrolyte material and the punch upper portion 301 ( Figure 3 The cross-sectional area of the hollow part of the frame mold 302 is equal to that of the hollow part of the frame mold 302). SE represents the resistance value of the solid electrolyte material in the impedance measurement. t represents the thickness of the solid electrolyte material (i.e., Figure 3 ), the thickness of the layer formed by the powder 101 of the solid electrolyte material.
[0140] The ionic conductivity of the solid electrolyte material of Example 1 measured at 25°C was 1.30×10 -6 S / cm.
[0141] (Battery production)
[0142] In a dry argon atmosphere, the solid electrolyte material of Example 1 and LiCoO2 as an active material were prepared in a volume ratio of 30:70 and mixed in an agate mortar to obtain a positive electrode mixture.
[0143] Next, LiCl and YCl3 were prepared in a molar ratio of LiCl:YCl3=3:1. These materials were crushed and mixed in a mortar. The resulting mixture was ground at 500 rpm using a planetary ball mill for 12 hours. In this way, a halide solid electrolyte (hereinafter referred to as "LYC") having a composition represented by Li3YCl6 was obtained.
[0144] In an insulating cylinder having an inner diameter of 9.5 mm, LYC (70 mg), the solid electrolyte material of Example 1 (33 mg), and the above-mentioned positive electrode mixture (9.1 mg) were stacked in this order. A pressure of 300 MPa was applied to the obtained stack to form a second electrolyte layer formed by LYC, a first electrolyte layer formed by the solid electrolyte material of Example 1, and a positive electrode. In other words, the first electrolyte layer formed by the solid electrolyte material of Example 1 was sandwiched between the second electrolyte layer and the positive electrode. The thicknesses of the second electrolyte layer and the first electrolyte layer were 450 μm and 150 μm, respectively.
[0145] Next, metal In (thickness: 200 μm) was stacked on the second electrolyte layer, and a pressure of 80 MPa was applied to the obtained stack to form a negative electrode.
[0146] Next, a current collector made of stainless steel was attached to the positive electrode and the negative electrode, and a current collecting lead was attached to the current collector.
[0147] Finally, an insulating hoop was used to isolate the inside of the insulating tube from the outside atmosphere, thereby sealing the inside of the tube. In this way, the battery of Example 1 was obtained.
[0148] (Charge and discharge test)
[0149] Figure 5 This is a graph showing the initial discharge characteristics of the battery of Example 1. The initial charge and discharge characteristics were measured by the following method.
[0150] The battery of Example 1 was placed in a constant temperature chamber at 85°C.
[0151] At 27μA / cm 2 The battery of Example 1 was charged at a current density of 0.02C until a voltage of 3.6 V was reached. This current density is equivalent to a 0.02C rate.
[0152] Next, at 27 μA / cm 2The battery of Example 1 was discharged at a current density of 1.9 V until a voltage of 1.9 V was reached.
[0153] The results of the charge and discharge test showed that the battery of Example 1 had an initial discharge capacity of 608 μAh.
[0154] <Examples 2 to 18>
[0155] (Production of solid electrolyte materials)
[0156] In Examples 2 to 18, LiF, ZrF4 and AlF3 were prepared as raw material powders in such a manner as to achieve a molar ratio of LiF:ZrF4:AlF3=[6-(4-x)b]:(1-x)b:xb.
[0157] Solid electrolyte materials of Examples 2 to 18 were obtained in the same manner as in Example 1 except for the above matters.
[0158] Table 1 shows the values of x, b, and the Li / (Zr+Al) molar ratio for the solid electrolyte materials of Examples 2 to 18.
[0159] (Evaluation of ion conductivity)
[0160] The ion conductivity of the solid electrolyte materials of Examples 2 to 18 was measured in the same manner as in Example 1. Table 1 shows the measurement results.
[0161] (Charge and discharge test)
[0162] Batteries of Examples 2 to 18 were obtained in the same manner as in Example 1 using the solid electrolyte materials of Examples 2 to 18.
[0163] The batteries of Examples 2 to 18 were subjected to charge and discharge tests in the same manner as in Example 1. The batteries of Examples 2 to 18, like the battery of Example 1, were able to be charged and discharged satisfactorily.
[0164] <Comparative Example 1>
[0165] As a solid electrolyte material, replacing Li 2.64 Zr 0.48 Al 0.48 F6 instead of LiBF4.
[0166] The ion conductivity of LiBF4 was measured in the same manner as in Example 1. The ion conductivity measured at 25°C was 6.67×10 -9 S / cm.
[0167] A battery of Comparative Example 1 was obtained in the same manner as in Example 1 using LiBF 4 as a solid electrolyte material.
[0168] The battery of Comparative Example 1 was subjected to a charge and discharge test in the same manner as in Example 1. As a result, the battery of Comparative Example 1 had an initial discharge capacity of 0.01 μAh or less. In other words, the battery of Comparative Example 1 could not be charged or discharged.
[0169] Table 1 shows the solid electrolyte materials in Examples 1 to 18 and Comparative Example 1 and the evaluation results.
[0170] Table 1
[0171]
[0172] <Inspection>
[0173] The solid electrolyte materials of Examples 1 to 18 have a strength of 8×10 -9 S / cm or higher ion conductivity.
[0174] Comparison between Examples 2 to 6 and Example 14 and Example 13 shows that the solid electrolyte material has higher ion conductivity as long as the value of x is 0.2 or more and 0.95 or less.
[0175] Comparison between Examples 1, 2, 7 and 9 and Examples 8, 10, 11, 15 and 16 shows that the solid electrolyte material has higher ion conductivity as long as the value of b is 0.9 or more and 1.04 or less.
[0176] The batteries of Examples 1 to 18 were all able to be charged and discharged at 85° C. On the other hand, the battery of Comparative Example 1 was not able to be charged and discharged.
[0177] The solid electrolyte materials of Examples 1 to 18 do not contain sulfur and thus do not generate hydrogen sulfide.
[0178] As described above, the solid electrolyte material of the present disclosure is suitable for providing a battery having high lithium ion conductivity and capable of good charge and discharge.
[0179] Industrial Applicability
[0180] The solid electrolyte material disclosed in the present invention can be used in, for example, an all-solid lithium-ion secondary battery.
Claims
1. A solid electrolyte material represented by the following composition formula (1): Li 6-(4-x)b (Zr 1-x Al x ) b F6 type (1) Here, the mathematical formulas: 0<x<1 and 0<b≤1.5 are satisfied.
2. The solid electrolyte material according to claim 1, wherein The ratio of the amount of Li to the total amount of Zr and Al is 1.12 or more and 5.07 or less.
3. The solid electrolyte material according to claim 1, wherein Satisfies the mathematical formula: 0.01≤x≤0.
99.
4. The solid electrolyte material according to claim 3, wherein Satisfies the mathematical formula: 0.2≤x≤0.
95.
5. The solid electrolyte material according to claim 1, wherein Satisfies the mathematical formula: 0.7≤b≤1.
3.
6. The solid electrolyte material according to claim 5, wherein Satisfies the mathematical formula: 0.9≤b≤1.
04.
7. A battery comprising: positive electrode, Negative electrode, and an electrolyte layer disposed between the positive electrode and the negative electrode; At least one selected from the positive electrode, the negative electrode, and the electrolyte layer contains the solid electrolyte material according to any one of claims 1 to 6.
8. The battery according to claim 7, wherein The electrolyte layer includes a first electrolyte layer and a second electrolyte layer, The first electrolyte layer is disposed between the positive electrode and the negative electrode, The second electrolyte layer is disposed between the first electrolyte layer and the negative electrode. The first electrolyte layer contains the solid electrolyte material.
Citation Information
Patent Citations
Lithium secondary battery and electrode for lithium secondary battery
JP2008277170A
Method of manufacturing sulfide solid electrolyte material, sulfide solid electrolyte material, and lithium battery
JP2011129312A
Solid electrolyte material and battery
WO2019146218A1